PABRIK DIETIL MALONAT DARI NATRIUM MALONAT DAN ETANOL KAPASITAS 30.000 TON/TAHUN - , FISKA YOHANA P, Ir. Moh Fahrurrozi, M.Sc.,Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Diethyl malonate is an organic ester compound with the molecular formula CH2(COOC2H5)2. It is used as raw material for pharmaceutical industry, vitamins, and agrochemicals. The demand of diethyl malonate in industry led to the need to build a new diethyl malonate plant in Indonesia.. The production process of diethyl malonate consists of sodium malonate dissolving, acid reaction, esterification reaction, process of separation, and purification products. The production facility of diethyl malonate is designed with the capacity of 30,000 tons/year and operated continuously for 330 days per year. Production process of diethyl malonate with a purity of 99.5% requires sodium malonate as much as 27,806 tons/year, ethanol 95% as much as 17.422,50 tons/year, sulfuric acid 98% as much as 18.788,08 tons/year, and benzene as a solvent as much as 1053,36 tons/year. In addition, the utility is required in the form of water as much as 30.029 kg/hour, steam as much as 2.989,78 kg/hour, fuel as much as 15.021 kg/hour, and the power of 349,38kW. The plant will be established in Gresik, East Java, with an area of 70,000 m2 and number of employees 200 people. The economic evaluation shows that Fixed Capital Investment is US$ 13,746,716.46 + Rp. 284.032.181.200,00